Special Issue “Working Group in Sports Medicine” - Giuseppe Musumeci (Journal of Functional Morphology and Kinesiology)
The Special Issue “Working Group in Sports Medicine” has been successfully concluded, offering significant contributions to the growing discourse on sports medicine as a dynamic and interdisciplinary field [...]